Investigation into barriers to adoption of e-procurement and measures of performance. (1st January 2012) - Gupta, Manish; Narain, Rakesh
Electronic procurement (e-procurement) is the purchase of goods and services through internet or any other electronic medium. This paper reports the findings of a survey carried out in 36 Indian organisations to investigate the barriers related to the adoption of e-procurement and the effect of e-procurement on performance measures in Indian scenario. The findings of this paper suggest that the main barriers to the adoption of e-procurement are: 1 economic and cultural barriers 2 socio-political barriers 3 cognitive barriers. There are many challenges in performance measurement of e-procurement systems like: lack of understanding of benefits of performance measurement, indicators not linked with the organisational objectives, and difficulty in information collection for performance measurement. There exist many factors that affect the performance by the implementation of e-procurement, and can be grouped into three categories: 1 reduced costs 2 increased performance 3 reduced number of suppliers.